GRAMD1-mediated accessible cholesterol sensing and transport - Naito, Tomoki (2022)
Cholesterol, an essential lipid for cell signaling and structural integrity of cellular membranes, is highly enriched in the plasma membrane (PM). However, the regulatory mechanisms that control its biosynthesis and uptake both reside in the endoplasmic reticulum (ER). Thus, the ER needs to constantly monitor the levels of PM cholesterol. This is in part mediated by regulated transport of a biochemically defined pool of cholesterol, termed "accessible" cholesterol, from the PM to the ER via evolutionarily conserved ER-anchored lipid transfer proteins, the GRAMD1s/Asters (GRAMD1a/1b/1c) (Lam/Ltc proteins in yeast). GRAMD1s possess cytosolically exposed GRAM domain and StART-like domain followed by a transmembrane ER anchor. They form homo- and hetero-meric complexes and move to the contacts formed between the ER and the PM by sensing a transient expansion of the accessible pool of cholesterol in the PM via the GRAM domain and facilitate its extraction and transport to the ER via the StART-like domain. The GRAMD1b GRAM domain possesses distinct, but synergistic sites, for recognizing accessible cholesterol and anionic lipids, including phosphatidylserine, within the PM. This property of the GRAM domain contributes to regulated tethering of the PM to ER membrane where GRAMD1s are anchored and fine-tunes StART-like domain-dependent accessible cholesterol transport. Thus, cells use GRAMD1s to sense the levels of cholesterol in the PM and regulate transport of accessible PM cholesterol to the ER in order to maintain cholesterol homeostasis.